Research trends in biogeography - Richard J. Ladle; Ana C. M. Malhado; Ricardo A. Correia; Jhonatan Guedes dos Santos; Ana M. C. Santos (Journal of Biogeography, 2015)
In a recent editorial, Whittaker (2014, Journal of Biogeography , 41 , 1–5) suggested that biogeography is in the process of adopting a ‘big science’ model, characterized by increasing levels of individual specialization and international collaboration. Using network analysis based on co‐authored articles and bibliometrics, we trace this transformation, identifying where biogeographical knowledge is produced and how the global biogeography community is connected. Our data reveal dramatic increases in biogeographical research over the last 30 years, with a trend of increasing diversity of countries and institutions. Moreover, an analysis of keywords suggests that the widening availability of molecular phylogenies and the ubiquitous threat of climate change are increasingly driving biogeographical research agendas. These trends are associated with diverse social and technological forces, notably advances in communication technology and the increasing availability and quality of biogeographical data.